2018
DOI: 10.1186/s13075-018-1670-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transitional care on self-care, readmission rates, and quality of life in adult patients with systemic lupus erythematosus: a randomized controlled trial

Abstract: BackgroundLack of adequate self-care, frequent admissions, and poor quality of life are common and serious problems in adult patients with systemic lupus erythematosus (SLE). Some studies have revealed that transitional care is effective in improving self-care and quality of life as well as reducing rehospitalization rates. However, limited studies explored its effects in adult patients with SLE. Therefore, we performed a study to examine the effects of transitional care on self-care, readmission rates, and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…Haro et al 22 reported that patients with SLE had a lower healthcare utilization rate, lower medication usage, and lack of rheumatology follow‐up after transition. Xie et al 23 noted that transitional care improved self‐care and quality of life, and decreased the hospital readmission rate. In the present study, we could not find any association between age, gender and TRAQ total score; while all female patients had higher TRAQ self‐management domain scores, and FMF patients who were colchicine‐resistant and treated with monthly canakinumab, and patients with active disease (3 SLE and 1 BD patients) at the time TRAQ was administered had lower total TRAQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…Haro et al 22 reported that patients with SLE had a lower healthcare utilization rate, lower medication usage, and lack of rheumatology follow‐up after transition. Xie et al 23 noted that transitional care improved self‐care and quality of life, and decreased the hospital readmission rate. In the present study, we could not find any association between age, gender and TRAQ total score; while all female patients had higher TRAQ self‐management domain scores, and FMF patients who were colchicine‐resistant and treated with monthly canakinumab, and patients with active disease (3 SLE and 1 BD patients) at the time TRAQ was administered had lower total TRAQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…While there are prior studies describing the problem of high readmission rates among SLE patients and risk factors for readmission, this is one of the first studies to look at an intervention to reduce the number of hospital readmissions. The study by Xie et al (11) assessed a transitional-care intervention to improve readmission rates among SLE patients. This study found a significant reduction in readmissions of patients with SLE who received the transitional-care model.…”
Section: Discussionmentioning
confidence: 99%
“…While there was likely overall cost savings with reduced hospital readmissions, the transitional-care model described in that study is a time and cost-intensive intervention. The model described by Xie et al (11) entails 4 in-person assessments and 4 phone calls per hospital discharge. In contrast, our model requires completion of a standardized template in the EMR and a single telephone call, and hence, may represent a more feasible intervention for clinics with limited resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations